Description of Hydraena (s.str.) tekmanensis (Coleoptera: Hydraenidae) from northeastern Turkey - Jäch, Manfred A.; Skale, Andre; Kasapoğlu, Ahmet (Zootaxa, 2011)
Hydraena (s.str.) tekmanensis sp. n. is described from northeastern Turkey (Erzincan and Erzurum Provinces). It is tentatively assigned to the H. rufipes group (H. eichleri complex).